The clinical outcomes of reni-angiotensin system inhibitors for patients after transcatheter aortic valve replacement: A systematic review and meta-analysis - Wang, Shuai; Lin, Xiaoxiao; Guan, Yihong; Huang, Jinyu (Frontiers in Cardiovascular Medicine, 2022)
Aims: The objective of our systematic reviews and meta-analysis is to evaluate the clinical outcomes of RAS inhibitors for patients after TAVR. Methods and results: We performed a comprehensive search for Embase, Pubmed, and Cochrane databases from inception to May 1, 2022. The analysis of all outcomes was performed using the random-effects model. In total, 7 articles with a total of 32585 patients (RAS inhibitor, N=14871; Controls, N=17714) were included in our study. There was a significantly lower rates of all-cause mortality (RR=0.76, 95%Cl=0.68 to 0.86, P<0.01), cardiovascular death (RR=0.66, 95%Cl=0.59 to 0.74, P<0.01) and HF readmission (RR=0.87, 95%Cl=0.80 to 0.94, P<0.01) in patients with RAS inhibitors compared with controls. Patients with RAS inhibitors also had lower rates of all-cause mortality (RR=0.82, 95%Cl=0.76 to 0.89, P<0.01) and cardiovascular death (RR=0.73, 95%Cl, 0.62 to 0.85, P<0.01) after propensity matching. Conclusions: In conclusion, our systematic reviews and meta-analysis demonstrated that RAS inhibitors could improve the clinical outcomes for patients after TAVR. Further large and high-quality trials should be conducted to support the use of RAS inhibitors for patients after TAVR.